Insolvency and Bankruptcy Code, 2016: A Critical Study - Sinha, Shivangi; Khandare, Jayashree (International Journal of Psychosocial Rehabilitation, 2020)
Ours is a developing nation, because of which many a things in our country is experimented with time and implemented. One such law is the “Insolvency and Bankruptcy Code of 2016”. The terms “insolvency” and “bankruptcy” are not synonyms to each other, but are used together. Insolvency basically defines „a state of being insolvent‟ or rather we can say a state of being an economic distress, whereas bankruptcy is a scenario where the court gives the order that how the insolvent situation will be dealt further. These orders basically consist of the ideas that how to erase the debts, and how to pay the unpaid creditors. The view of this is very simple; this is formulated to deal with situations of failure, which is very natural when any investor/people step into the commercial world. The vision of this law basically encourages various small scale industries and start ups to function swiftly and handle their financial issues in their own sweet very ways. One more aspect of the formulation of this law is to create a huge umbrella and bring all the other statutes dealing with the same issues, and to bring them under one entire head and function. This simplification of laws will not only help the new players to enter into the market but will also help the existing entrepreneurs to move on, rather than blogging off with old legislations and decisions. Hopefully, the implication of this law can move India little ahead in the ease of doing business index ranking and can attract more investors from far. This article is basically going to focus on the very ground root aspects of this legislation i.e., even after having so many commercial laws why do we need one such law on Insolvency and Bankruptcy? How is this helpful at our current situation, moreover what is the objective of this act to get formulated with some illustrations. At higher level various commercial and corporate laws are formulated for us, but because of the lack of understanding we are not able to understand and use it where required. This article will try and fill up those lacunas about this newly constructed law in further discussions.